Women's Perspectives on the Context of Violence and Role of Police in Their Intimate Partner Violence Arrest Experiences. (February 2015) - Li, Simiao; Levick, Ani; Eichman, Adelaide; Chang, Judy C.
Intimate partner violence (IPV) accounts for up to 50% of all calls to police. In an effort to standardize arrest criteria, mandatory arrest laws were established. It is unclear whether subsequent increased rates of female arrest are due to greater recognition of female IPV perpetrators or of women acting in self-defense. This study aims to understand the context and consequences of IPV-related arrest from perspectives of women arrested in a single metropolitan area. Semi-structured qualitative interviews were conducted with women arrested and court-ordered to attend IPV education groups at a women's shelter in the Northeast United States. Interviews addressed circumstances surrounding arrest, experience with past violence, and reasoning regarding use of partner violence. Two researchers independently coded transcripts and met to iteratively refine the code and review transcripts for themes. Eighteen women were interviewed. Major themes that emerged were as follows: (a) Women's use of violence occurred within the context of their own victimization; (b) the arrest included a complex interplay between subject, partner, and police; (c) women perceived police arrest decisions to be based on a limited understanding of context; and (d) women experienced both positive and negative consequences of arrest. Many relationships did not fall under the traditional victim/perpetrator construct. Rather, women's use of violence evolved, influenced by prior experiences with violence. More appropriate methods must be developed for making arrest decisions, guiding justice system responses, and developing interventions for couples experiencing IPV. Recognition that women's use of partner violence often represented either a retaliatory or self-defensive gesture within the context of prior victimization suggests that victims' interventions should not only focus on empowerment but also provide skills and strategies to avoid temptation to adopt aggression as a primary method of self-protection.